EFFECTS OF COGNITIVE RESTRUCTURING AND PROBLEM SOLVING STRATEGIES ON READING AND NOTE TAKING OF SECONDARY SCHOOL STUDENTS IN ONDO STATE, NIGERIA - Segun, Olowolabi (Advances in Social Sciences Research Journal, 2017)
ABSTRACT The recurring problem of low academic achievement among secondary school students has been attributed to many factors among which are poor reading skills and note taking behavior which are the concern of this study. The study investigated the effects of cognitive restructuring and problem-solving strategies in the treatment of poor reading skills and note taking among secondary school students in Ondo State. The study adopted quasi experimental pre-test, post-test and control group research design. One hundred and twenty subjects (120) were selected through purposive and stratified random sampling techniques from three secondary schools in Ondo state. One school from each of three senatorial districts of Ondo State. Samples were assigned to three groups: cognitive restructuring, problem–solving and control groups. Each group consisted of forty subjects. Instrument used for the study was Study Habit Inventory (SHI) adapted from Bakare’s Study Habit Inventory (1977). Two hypotheses were tested at 0.05 alpha level. Data collected were analyzed using analysis of co-variance (ANCOVA). Results of the study revealed that there was significant difference in the reading and note taking of experimental group and control group. The treatment strategies: Cognitive Restructuring and Problem-Solving techniques assisted in improving reading and note taking of the respondents. Based on the findings, it was concluded that application of Cognitive Restructuring and Problem-solving Strategies are capable of ameliorating poor reading skills and note taking of secondary school students. Therefore, it was recommended that Teachers, Counsellors, Psychologists, and other stakeholders in education need to embark upon administering cognitive restructuring and problem-solving strategies by training of stakeholders on the two strategies so as to improve reading skills and note-taking to enhance reading culture and good academic performance among students. Keywords: cognitive restructuring, problem solving strategy, note-taking, reading skills.